Cyberbullying and Detection Methods - Yazgili, Enver; Baykara, Muhammet (Institute of Electrical and Electronics Engineers Inc., 2019)
One of the major problems of our time, cyber bullying is increasing day by day. It is very difficult to identify this type of bullying which causes great difficulties for its victims and sometimes leads them to suicide. The widespread use of the Internet extends the scope of cyberbullying. As a result, social networks, platforms and sharing sites using can apply cyber bullying more than classical bullying with the self-confidence that the crimes they will commit cannot be detected and they will not face any sanctions even if they are detected. Various studies have been carried out in the literature to identify this problem. In this study, firstly, what is cyber bullying, types, prevention and detection of what kind of studies are carried out in the literature and cyber bullying detection methods are presented. © 2019 IEEE.
Siber Zorbalik ve Tespit Yöntemleri
1st International Informatics and Software Engineering Conference, IISEC 2019 -- 6 November 2019 through 7 November 2019 -- Ankara -- 157111
Keywords: cyber bullying; cyber crime; cyber security; Information security